Gas hydrate dissociation prolongs acidification of the Anthropocene oceans - Boudreau, B.P.; Luo, Yiming; Meysman, Filip J R; Middelburg, J.J.; Dickens, G.R. (John Wiley and Sons Inc., 2015)
Anthropogenic warming of the oceans can release methane (CH4) currently stored in sediments as gas hydrates. This CH4 will be oxidized to CO2, thus increasing the acidification of the oceans. We employ a biogeochemical model of the multimillennial carbon cycle to determine the evolution of the oceanic dissolved carbonate system over the next 13 kyr in response to CO2 from gas hydrates, combined with a reasonable scenario for long-term anthropogenic CO2 emissions. Hydrate-derived CO2 will appreciably delay the neutralization of ocean acidity and the return to preindustrial-like conditions. This finding is the same with CH4 release and oxidation in either the deep ocean or the atmosphere. A change in CaCO3 export, coupled to CH4 release, would intensify the transient rise of the carbonate compensation depth, without producing any changes to the long-term evolution of the carbonate system. Overall, gas hydrate destabilization implies a moderate additional perturbation to the carbonate system of the Anthropocene oceans.